The effect of ethnicity on the age-related changes of spinopelvic characteristics: a systematic review - Kenneth J. Lukas; Jeroen C. F. Verhaegen; Holly Livock; Erik Kowalski; Philippe Phan; George Grammatopoulos (Bone & Joint Research, 2023)
Aims: Spinopelvic characteristics influence the hip’s biomechanical behaviour. However, to date there is little knowledge defining what ‘normal’ spinopelvic characteristics are. This study aims to determine how static spinopelvic characteristics change with age and ethnicity among asymptomatic, healthy individuals. Methods: This systematic review followed the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines to identify English studies, including ≥ 18-year-old participants, without evidence of hip or spine pathology or a history of previous surgery or interventional treatment, documenting lumbar lordosis (LL), sacral slope (SS), pelvic tilt (PT), and pelvic incidence (PI). From a total of 2,543 articles retrieved after the initial database search, 61 articles were eventually selected for data extraction. Results: When all ethnicities were combined the mean values for LL, SS, PT, and PI were: 47.4° (SD 11.0°), 35.8° (SD 7.8°), 14.0° (SD 7.2°), and 48.8° (SD 10°), respectively. LL, SS, and PT had statistically significant (p < 0.001) changes per decade at: −1.5° (SD 0.3°), −1.3° (SD 0.3°), and 1.4° (SD 0.1°). Asian populations had the largest age-dependent change in LL, SS, and PT compared to any other ethnicity per decade at: −1.3° (SD 0.3°) to −0.5° (SD 1.3°), –1.2° (SD 0.2°) to −0.3° (SD 0.3°), and 1.7° (SD 0.2°) versus 1.1° (SD 0.1°), respectively. Conclusion: Ageing alters the orientation between the spine and pelvis, causing LL, SS, and PT to modify their orientations in a compensatory mechanism to maintain sagittal alignment for balance when standing. Asian populations have the largest degree of age-dependent change to their spinopelvic parameters compared to any other ethnicity, likely due to their lower PI. Cite this article: Bone Joint Res 2023;12(4):231–244.